Impact of country effects on the performance of service firms. Issue 4 (17th August 2015) - Elango, B; Wieland, Jamie R.
Abstract : Purpose: – Understanding the impact of country effect on financial performance is important for service firms as they continue to grow and operate across national borders. The purpose of this paper is to empirically quantify the impact of country and several country-specific variables on firm performance in the service sector by estimating the portion of variation in firm performance attributed to these factors. Design/methodology/approach: – Using hierarchical linear models, the authors estimate the proportion of variation driven by country effects. These estimates are obtained from a data panel of 16, 051 units from 3, 345 service firms across 32 countries over a seven-year time frame (2001-2007). Findings: – In the analysis, home country explains approximately 11 percent of the variance in performance. Additionally, the authors find that six country-specific variables, namely, quality of governance, openness to trade, wealth, growth rate, uncertainty avoidance and individualism collectively explain 10 percent of variation in performance or 26.8 percent relative variation of performance. Originality/value: – This study extends the literature on country effect by quantifying the impact of country-specific dimensions on performance. It focusses on a single industry within the service sector. This allows for a more reliable estimate of the country effect, as it will not be confounded by cross-industry effects – thus alleviating some of the concerns with earlier research. Understanding the impact of the six specific country variables investigated in this work will allow service firms to better predict and improve the performance of subsidiaries.